Newly discovered Slavic lexical borrowings in documents from the 15th-17th centuries of the Polish-Armenian colony - Khachatryan, Gurgen; Trzeciak, Łukasz (Przegląd Wschodnioeuropejski, 2025)
The documents of the Polish-Armenian colony, deposited between the 15th and the 17th centuries, are distinguished by their content diversity. These documents include a range of direct and indirect borrowings from Slavic languages, particularly from Old/Middle Polish and Middle Ukrainian, the vast majority of which (more than 200 word units) are included in linguistic studies. However, on the basis of our observations, for various reasons, more than 50 word units have been left out of the attention of specialists engaged in the study of the vocabulary of the Middle Armenian language. In this article, we have studied around 20 newly discovered borrowings and have come to a number of conclusions. The examined newly discovered borrowings are also noteworthy because they did not have a pan-Armenian distribution. They were used only in the Polish-Armenians’ speech relating to various aspects of social life, which effectively attests to the Polish-Armenians’ integration into the new environment.